Analisis Penerapan Penggunaan Mufradat dalam Komunikasi Bahasa Arab di Pondok Pesantren Islamic Center eLKISI Mojokerto - Yusrinawati, Azifa; Ammar, Farikh Marzuki (Academicia Globe: Inderscience Research, 2020)
Mufradat has an important role in communication skills. This research is motivated by the difficulties of Arabic language boarding students at the Mojokerto eLKISI Islamic Center Islamic Boarding School in applying mufradat when communicating. The purpose of this study was to find out the application of mufradat for female students in Arabic dormitories communication, to examine the difficulties of students in applying mufradat when communicating in Arabic, and alternative solutions to these problems. This type of research is a descriptive-qualitative study with research subjects being female students of the Arabic boarding school, Mudabbir, and Ismul Lughah. Research data was collected through interviews, observation, and documentation. The results of the study show that some students still use Indonesian and do not apply mufradat in communication. There are two linguistic difficulties and four non-linguistic difficulties. Two linguistic difficulties are in the form of a lack of mastery of grammar and knowledge of grammar. Four non-linguistic difficulties in the form of a less supportive social environment in the dormitory, different class backgrounds, limited time for students' activities in the dormitory, and the emergence of a sense of shame and fear of being wrong. The solution to this problem is implementing a mandatory language program for all students, maximizing the role of Mudabbir as a facilitator and linguistic role model, and implementing a reward and punishment system.